Υπολογιστική προσομοίωση διάδοσης φωτιάς σε κτίριο με συστήματα ξηράς δόμησης και με υλικά αλλαγής φάσης - Ασημακοπούλου, Ελένη Μαρίνα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών, 2011)
A contemporary technique to increase the thermal mass of a building element is to incorporate a Phase Change Material (PCM) into its volume; in this case, the thermal energy absorbed (or released) during the PCM’s transition from solid to liquid phase (or vice-versa) results in a reduction of the indoor temperature fluctuations, thus affecting favourably the required total energy consumption for heating and air-conditioning purposes. Recently, gypsum plasterboards incorporating paraffin-based PCMs, encapsulated in millimetre scale polymer spheres, have become commercially available. The solid-liquid phase change occurs in the temperature range typically found in indoor environments (20-26 C). However, in the event of a fire, building materials may be exposed to substantially higher temperatures (over 800 C). In this case, the paraffins, exhibiting boiling points below 350 C, are expected to evaporate; if the encapsulation spheres fail, the produced paraffin vapours will be released to the porous structure of the gypsum plasterboard and, through mass diffusion, will emerge to the fire region, where they will ignite, thus adversely affecting the fire resistance characteristics of the building. The effect of PCM addition is investigated by performing detailed numerical simulations of the developing flow and thermal fields in a building constructed using gypsum plasterboards and exposed to fire conditions. The FDS code is used to simulate the turbulent, multicomponent and reactive flow-field developing inside a prototype building in Amfilohia. The examined building is constructed using a structural steel frame configuration with dry-wall systems. The internal and external walls consist of various layers of gypsumboard, cementboard and insulating materials. When a gypsumboard is subjected to a high temperature environment, water molecules bound in its crystal latice are released and transferred through the board, absorbing energy and thus reducing the mean wall temperature; this process is known to enhance the fire resistance characteristics of the structure. The actual thermophysical properties of all the construction and furniture house materials are taken into account, in order to accurately describe their thermal behaviour. The simulated two-storey building is considered to be completely furnished according to a standard residential configuration. The fire resistance behaviour of the building is further evaluated by considering two realistic alternative ventilation scenarios and three different technique methods. Numerical predictions of the temporal evolution of various parameters such as gas velocity, gas and wall temperatures, toxic gas concentrations and smoke movement are obtained for the entire domain that represents the interior of the building. Gas velocity and temperature predictions are used to visualize the developing flow-field and to estimate the heat flux that each building element is exposed to. Predicted wall temperatures allow the assessment of the steel frame – dry-wall construction technique in terms of fire resistance. The temperature variation of the various materials’ thermo-physical properties is taken into account by using information obtained by means of Differential Scanning Calorimetry. A conjugate heat transfer model is used to calculate the dynamically varying wall temperature; the paraffin evaporation process is modelled and the produced vapours are introduced to the flow-field as an additional gaseous “fuel” source. The CFD code is validated by utilising available experimental data, obtained in a standard ISO 9705 fire room exposed to an n-heptane pool fire.